Kinematic Profile of the Sideways Shot Put Technique: Baseline Data for Indonesian Athletes (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
Shot put performance in Indonesia significantly lags behind Asian standards (27.5% gap), hindered by the absence of population-specific kinematic data for evidence-based training development. This study aimed to establish normative kinematic parameters for Indonesian shot put athletes by using the glide technique and examine relationships between technical consistency and throwing performance. A cross-sectional observational study analyzed 16 regional-level shot put athletes from Central Java (9 males, 7 females; aged 18.9±2.0 years) during provincial championships. The two best trials per athlete were analyzed using 2D kinematic analysis with Kinovea software (120 fps). The primary parameters measured were release velocity, release angle, release height, and trunk rotation angle. Technical consistency was assessed via Average Relative Error (ARE) and coefficient of variation (CV%). Pearson correlation examined relationships between parameter variability and throwing distance. The analysis of kinematic mean values showed a release velocity of 11.01±1.18 m/s, a release angle of 37.5±3.2°, a release height of 2.02±0.13 m, and trunk rotation of 41.4±5.4°, with a mean throwing distance of 12.28±1.68 m. Central Java athletes demonstrated 18.4% lower release velocity compared to elite Asian athletes (11.01 vs. 12.80 m/s). Fundamental parameters showed low variability (ARE 8%), whereas trunk rotation exhibited higher inconsistency (ARE 21.4%). Significant inverse correlations were found between variability and performance for release velocity ARE (r = −0.624, p=0.009), release angle ARE (r = −0.542, p = 0.031), and trunk rotation ARE (r = −0.687, p=0.003). Athletes with ARE 10% on key parameters achieved 15.8% greater throwing distances than those with higher variability (13.2 m vs. 11.4 m). This study provides the first-ever normative kinematic data for Indonesian shot put athletes, revealing substantial performance gaps compared to international standards. Technical consistency, particularly in trunk rotation and release velocity, strongly influences throwing performance. The established reference values and performance zones enable evidence-based talent identification, technique assessment, and training program design for regional-level athletes.